Structural damage identification using an enhanced thermal exchange optimization algorithm. Issue 3 (4th March 2018) - Kaveh, A.; Dadras, A.
ABSTRACT: The recently developed optimization algorithm—the so-called thermal exchange optimization (TEO) algorithm—is enhanced and applied to a damage detection problem. An offline parameter tuning approach is utilized to set the internal parameters of the TEO, resulting in the enhanced heat transfer optimization (ETEO) algorithm. The damage detection problem is defined as an inverse problem, and ETEO is applied to a wide range of structures. Several scenarios with noise and noise-free modal data are tested and the locations and extents of damages are identified with good accuracy.